A “Middle Power”s Diplomacy to its Vicinity: Caucasus Projection of Türkiye’s Regional Ownership Vision and 3+3 Platform - Turan, Ahmet (My University, 2024)
One of the prominent actors in the international system in terms of various classifications of power is the ‘middle power’. Another important issue related to this concept is ‘middle power diplomacy’. Although it has different and sometimes opposing distinctive features, Türkiye has the qualities of both a ‘middle power’ and an actor conducting ‘middle power diplomacy’. An important phenomenon within Türkiye’s foreign policy instruments is the concept of ‘regional ownership’. For Ankara, the vision of regional ownership manifests itself through different foreign policy instruments for various regions. The aim of this study is to analyse the 3+3 Platform within the framework of Türkiye’s vision of regional ownership. In this context, the study analyses the characteristics of the concept of ‘regional ownership’ in the literature and seeks an answer to the extent to which the 3+3 Platform meets these characteristics. Case analysis, one of the qualitative research methods, was used in the study. Accordingly, the study analyses the information, documents and reports shared by the official authorities of the countries that are parties to the 3+3 Platform, as well as the discourses of the high-level officials of these actors.
Keywords: Türkiye; Caucasus; Middle Power; Regional Ownership; 3+3 Platform